Sustainable fixation of CO2 into epoxides to form cyclic carbonates using hollow marigold CuCo2O4 spinel microspheres as a robust catalyst. Issue 16 (25th July 2019) - Prasad, Divya; Patil, Komal N.; Bhanushali, Jayesh T.; Nagaraja, Bhari Mallana; Jadhav, Arvind H.
Abstract : The present work demonstrates the chemical fixation of CO2 for the synthesis of organic carbonates using mesoporous hollow marigold CuCo2 O4 spinel microspheres as a catalyst prepared using the solvothermal method. Abstract : The present work demonstrates the chemical fixation of CO2 for the synthesis of organic carbonates using mesoporous hollow marigold CuCo2 O4 spinel microspheres as a catalyst prepared using the solvothermal method. The synthesized microspheres were characterized using contemporary analytical and spectroscopic tools. The CuCo2 O4 spinel microspheres with the best morphological behaviour obtained after solvothermal treatment for 3 h were employed as a heterogeneous catalyst for the solvent-free conversion of epoxides and CO2 to generate cyclic carbonates. As a result, the model reaction of styrene oxide and CO2 revealed 94% conversion, 88% yield and 94% selectivity towards styrene carbonate in the presence of TBAI as a base under mild reaction conditions (80 °C, 20 bar, 3 h). Notably, the enhanced catalytic activity was attributed to the cooperative effect of the exposed Lewis acidic sites of CuCo2 O4 and the efficient basic nature of TBAI. The effects of different reaction variables such as catalyst loading, temperature, pressure and time were investigated and discussed. Additionally, the effect of different bases was also experimentally determined. Further, the substrate scope using the CuCo2 O4 and TBAI catalytic system revealed good performance towards CO2 fixation with a variety of terminal and internal epoxides. The catalyst was easily separated out after the reaction and tested for its recyclability. Results showed good recyclability up to five cycles without a substantial loss of catalytic activity. Based on the results obtained from XPS, XRD, and TPD and the available literature, an effort to predict a plausible mechanism was made in order to support the cycloaddition reaction. The present protocol is the first report of hollow marigold CuCo2 O4 spinel microspheres as an outstanding and efficient catalyst with high selectivity towards fixation of CO2 into epoxides for cyclic carbonate formation.